The Development and Transformation of Judaism from Antiquity to Modernity - Muhammad Gilang Ramadhan; Fitri, Fitriani; Hafiz Hamdi Nasution (Prodi Sosiologi Agama, 2024)
This journal aims to investigate the evolution of Judaism from ancient times to the modern era. Through a meticulous historical approach, this research will explore shifts in beliefs, religious practices, and the impact of social, political, and cultural events on the development of Judaism from prehistoric times to the contemporary era. By integrating analyses of ancient texts, historical records, and interdisciplinary studies, this journal will discuss how Judaism has evolved, adapted, and maintained its identity in confronting the challenges of time. This study involves an analysis of the social, political, and cultural changes that have influenced Judaism throughout history. Utilizing historical methods, studies of religious texts, and interaction within its surrounding social context, this journal traces the transformation of Judaism from its inception to its influence on contemporary society.